America in an Arab Mirror - Juliane Hammer (International Institute of Islamic Thought, 2001)
How do Arab travelers view the US? Much has been written about how western travelers and scholars have seen and described the Orient, thereby not only creating an image but also transforming the reality of it. Looking at this anthology one is reminded of Said's book Orienta/ism and inspired to ask whether a similar process takes place in reverse. Not in terms of change but certainly in creating an image of the unfamiliar as the other simultaneously admired and rejected. Kamal Abdel-Malek has collected and edited texts of twenty-seven Arab visitors to the United States. Some came as students, others as accomplished scholars or curious visitors. Each text is an excerpt of a longer text, usually a book, and all books were originally published in Arabic and have not been translated into English before. Also, as Abdel-Malek points out in his preface, the collection represents most of the travel literature he was able to locate in Arabic and is completed by a list of all Arabic sources. Thus, this collection allows the reader access to a genre of Arabic literature otherwise not available. The travel accounts are organized in five sections and chronologically by year of publication within each section. The ftrst section is titled America in the Eyes of a Nineteenth-Century Amb and contains one account of an Arab traveler to the US published in I 895. The author presents the reader with a comparison of what Arabs and Americans find important and how these preferences are diametrically opposed in most cases. In the second section Abdel-Malek has gathered a variety of accounts under the title The Making of an Image: America as the Unchanged Other, Ame1ica as the Seductive Female. The most interesting piece of this section is probably that of Sayyid Qutb, who studied in the US between 1948 and 1950 and published his account under the title The America I have seen. Much of what he noted about the US ln the first half of the 20th century, in my opinion, still holds true today. Qutb concludes: "All that requires mind power and muscle are where American genius shines, and all that requires spirit and emotion are where American naivete and primitiveness become apparent .... All this does not mean that Americans are a nation devoid of virtue, or else, what would have enabled them to live? Rather, it means that America's virtues are the virtues of production and organization, and not those of human and social morals." (p. 26f.) ...